Judicialização da afetividade: análise de julgados do Supremo Tribunal Federal e Superior Tribunal de Justiça - Andrade, Lília de Sousa Nogueira (2024)
The research analyzes the presence of affectivity in the rulings of the Brazilian Supreme Court (STF) and the Superior Court of Justice (STJ). It conducts a documentary investigation, using the courts' own online databases to analyze rulings that mention the word "affectivity." The research employs both quantitative and qualitative approaches. The quantitative approach identifies the frequency with which the term "affectivity" appears in the rulings, while the qualitative analysis interprets the content of these decisions, examining how the concept is used. The quantitative research identifies the frequency of the term in judgments, single-judge decisions, summaries, and jurisprudence reports in both courts. The qualitative analysis classifies the rulings into five categories: "accidental," "not admitted," "relevant," "essential," and "not mentioned." It discusses the impracticality of inferring affectivity in the Brazilian legal system, arguing that there is no clear legal concept of affectivity. The courts treat affectivity in a varied and imprecise manner. The study argues that the use of the principle of affectivity may set precedents that legitimize undefined situations. It advocates that the law should be based on objective conduct, as established by the rules, rather than on feelings or emotions such as affectivity. It addresses two key issues: sentimentality in society and in law, and legal uncertainty. It concludes by affirming the absence of a legal concept of affectivity and proposes measures, such as the need to restore the concept of family, centered on social responsibilities and ethical duties. It highlights the importance of promoting a stronger ethical education for judges, based on classical virtues, to ensure they are equipped to apply the law without being influenced by subjectivism.